Total Quality Management Integration in Manufacturing Industry: Insights from ABX Company Case Study - Ahmad @ Mohamad, Md Fauzi; Chan, Shiau Wei; Ahmad, Ahmad Nur Aizat; Abdul Latip, Hamrila; Rashid, Nurulizwa (Research in Management of Technology and Business, 2024)
In today’s dynamic business landscape, organizations face the imperative to continually refine their operational frameworks. An avenue often explored for this purpose is the integration of Total Quality Management (TQM) principles into business methodologies. However, recognizing the factors and hurdles inherent in TQM implementation is pivotal for achieving success in this endeavor. This study endeavors to pinpoint the critical success factors crucial for TQM integration, focusing on a metal stamping manufacturing entity, with ABX company serving as the primary case study subject. Findings from the study underscore several key elements essential for effective TQM implementation, including unwavering management commitment and leadership, a culture of continuous improvement, paramount customer satisfaction, active employee engagement, comprehensive training initiatives, and robust communication and teamwork protocols. Notably, management commitment and leadership emerge as the foremost determinant of successful TQM integration. Furthermore, the study delves into the various barriers and challenges encountered by the company throughout the TQM implementation process. These impediments are thoroughly examined through a SWOT analysis framework, elucidating the strengths, weaknesses, opportunities, and threats inherent in the TQM adoption journey. By shedding light on the practical application of TQM within a manufacturing context and elucidating the attendant challenges, this research contributes significantly to enhancing comprehension of TQM implementation dynamics.